2020
DOI: 10.1093/jac/dkaa257
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale assessment of antimicrobial resistance marker databases for genetic phenotype prediction: a systematic review

Abstract: Background Antimicrobial resistance (AMR) is a rising health threat with 10 million annual casualties estimated by 2050. Appropriate treatment of infectious diseases with the right antibiotics reduces the spread of antibiotic resistance. Today, clinical practice relies on molecular and PCR techniques for pathogen identification and culture-based antibiotic susceptibility testing (AST). Recently, WGS has started to transform clinical microbiology, enabling prediction of resistance phenotypes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 48 publications
1
78
0
Order By: Relevance
“…In addition, F022 and F047 carry bla TEM-1 but vary in their cefotaxime resistance responses, suggesting that bla TEM-1 does not explain the variable resistance response. This is perhaps unsurprising as the prediction of a strain’s resistance phenotype from gene content alone is notoriously inaccurate ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, F022 and F047 carry bla TEM-1 but vary in their cefotaxime resistance responses, suggesting that bla TEM-1 does not explain the variable resistance response. This is perhaps unsurprising as the prediction of a strain’s resistance phenotype from gene content alone is notoriously inaccurate ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…As it is mandatory to use more than one public resistance database, we found that, using the ResFinder and CARD, some entries were exclusive to either one or the other: bla AmpS and bla AmpH only appeared in ResFinder and bla AQU-1 , bla AQU-2 , bla MOX-9 and bla CepS were exclusive to CARD. These specific entries yielded matches with higher identities for our query sequences, indicating that completeness is essential for proper diagnosis and that more than one curated database for antimicrobial resistance genes should be used when screening isolates [ 37 ]. Nevertheless, regarding Aeromonas resistance genes, both ResFinder and CARD are good tools for screening, but we found that the percentage of identity for many species-specific resistance genes, such as bla AmpC of A. hydrophila and bla OXA -like of A. caviae , was too low.…”
Section: Discussionmentioning
confidence: 99%
“…A large majority of the AMR genes detected in the E. coli ST38 isolate and across the E. coli isolate set were efflux-associated AMR genes. Efflux-associated genes are of uncertain relevance for prediction of microbial phenotypes 36,37 . In some scenarios (e.g.…”
Section: Discussionmentioning
confidence: 99%